RELATIONSHIP OF COMMORBID DISEASE TO MORTALITY EVENTS IN COVID-19 PATIENTS - Zahrul Azhar; Citra Tri Widyastuti; Khotimah Khotimah; Mukhamad Rajin; Diah Ayu Fatmawati; Herin Mawarti (International Journal of Social Science, 2021)
Background: Covid-19 is a disease caused by acute respiratory syndrome due to corona virus 2. Patients with Covid-19 experience symptoms of severe shortness of breath resulting in death. The risk of death for Covid-19 sufferers will be greater if the patient has a history of comorbid diseases such as hypertension, diabetes mellitus, cardiovascular disease or kidney disease.Objective: The purpose of this study was to determine the relationship between comorbid diseases and the incidence of mortality in patients with Covid-19.Method: Research design using descriptive analytic. The research population was all Covid-19 sufferers who were treated at Mojowarno Christian Hospital (RSK) during 2021 totaling 450 sufferers. The research sample was 212 respondents with a sampling technique using systematic random sampling. The data was obtained from the medical records of Covid-19 patients who were treated at the Mojowarno Hospital. Statistical test using chi square and odds ratio with a significance level of P <0.05. Results: The results of the study found that comorbid diabetes mellitus showed a result of P: 0.000, meaning that there was a relationship between comorbid diabetes mellitus and the incidence of mortality in patients with Covid-19. Comorbid kidney disease shows a P value: 0.003, meaning that there is a relationship between comorbid kidney disease and the occurrence of mortality in Covid-19 sufferers. Comorbid heart disease results obtained P: 0.089, meaning that there is no relationship between comorbid heart disease and mortality in patients with Covid-19. Hypertensive comorbid disease on mortality with a P value: 0.134 meaning that there is no relationship between hypertension comorbid disease and the risk of mortality in patients with Covid-19. Conclusion:Covid-19 sufferers who have comorbid diabetes mellitus cause greater mortality. This is because diabetes mellitus can cause a cytokine storm which plays a role in increasing the severity of COVID-19 sufferers so that it often causes death.